CeCl3·7H2O catalyzed C(sp2)−CN bond construction on water: Synthesis of (Z)-2-(2-Oxoindolin-3-ylidene)-2-arylacetonitriles. Issue 1 (2nd January 2019) - Du, Yan; Li, Zheng
Abstract: An environmentally friendly method for the construction of C(sp 2 )-CN bond on water has been described, and ( Z )-2-(2-oxoindolin-3-ylidene)-2-arylacetonitriles were synthesized by using CeCl3 · 7H2 O as a catalyst. The reaction offers access to alkenyl nitriles in good-to-excellent yield. The investigations will be beneficial to reduce the use of toxic organic solvents and explore the efficient catalytic processes on water. Graphical Abstract: